MODEL PERHITUNGAN ZAKAT PERTANIAN (Studi Di Kecamatan Kuta Makmur Aceh Utara) - Ainiah Abdullah (Universitas Islam Negeri Sumatera Utara, 2017)
This research aims to analize deeply about agriculture zakah accounting of rice plant in Kuta Makmur, North Aceh, and the factors that influenced people to choose that accounting model. This research is a field research in descriptive qualitative-inductive research. Primary data obtained through interviews while secondary data obtained through the literature study. The research results showed that the accounting model of agriculture zakah in Kuta Makmur, North Aceh is highly influenced with Shafiiyah and highly maintained and hard to shift with the other opinion and contemporary fatwa although the conditions and the situations demand it. Such as, the nishâb accounting model does not take into consideration of operational costs at all, the first harvest will add to the next harvest within a year in order to reach nishâb. That selected accounting model influenced by several factors such as theological factor, psychological factor, educational factor and socio-cultural factor.